2008
DOI: 10.1590/s0103-64402008000100005
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial effect and pH of chlorhexidine gel and calcium hydroxide alone and associated with other materials

Abstract: The purposes of this study were to evaluate the effectiveness of 2% chlorhexidine (CHX) gluconate gel, calcium hydroxide [Ca(OH) 2 ] and their combination with iodoform and zinc oxide powder as intracanal medications against select microorganisms, and to measure the pH changes caused by these medications. Antimicrobial activity was determined by the agar diffusion method. The zones of growth inhibition were measured and the results were analyzed statistically by Kruskal-Wallis test (p<0.05). The pH of the past… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
60
3
13

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(83 citation statements)
references
References 19 publications
7
60
3
13
Order By: Relevance
“…CHX has a reasonably wide range of activity against aerobic and anaerobic bacteria, as well as Candida species. Several studies have reported a better antimicrobial activity for CHX when used as an endodontic dressing, compared with CH and the association of CHX and CH (7)(8)(9). Although CHX is also a potent antimicrobial irrigant, its capacity of tissue dissolution is reduced and when in contact with a common endodontic irrigant, sodium hypochlorite, it results in a "potentially toxic precipitate" (10).…”
Section: Introductionmentioning
confidence: 99%
“…CHX has a reasonably wide range of activity against aerobic and anaerobic bacteria, as well as Candida species. Several studies have reported a better antimicrobial activity for CHX when used as an endodontic dressing, compared with CH and the association of CHX and CH (7)(8)(9). Although CHX is also a potent antimicrobial irrigant, its capacity of tissue dissolution is reduced and when in contact with a common endodontic irrigant, sodium hypochlorite, it results in a "potentially toxic precipitate" (10).…”
Section: Introductionmentioning
confidence: 99%
“…Endodontic filling with gutta-percha and sealer does not dissolve, differently from what occurs with this intracanal dressing paste, since it may dissolve at the same time as it comes into contact with the periapical tissues. This paste also demonstrated antimicrobial properties, and maintained alkaline pH for one week 25 . It is likely that after some weeks, only zinc oxide was present, since Ca(OH) 2 should have undergone complete dissolution 14 .…”
Section: Discussionmentioning
confidence: 89%
“…In this study, 2% chlorhexidine gel was used as auxiliary chemical substance. It was demonstrated that 2% chlorhexidine gel has excellent antimicrobial activity and is more biocompatible than sodium hypochlorite 25 .…”
Section: Discussionmentioning
confidence: 99%
“…There is another endothermic event smaller, which took place around 186°C. This is due to the fusion of chlorhexidine [17]. Pure gelatin has an endothermic peak ranging from 46°C to 160°C.…”
Section: Resultsmentioning
confidence: 99%